Sosialisasi Pencegahan Kekerasan terhadap Anak dan Perempuan dalam Perspektif Hukum Perlindungan Anak dan Perempuan di Nagari Kasang, Kecamatan Batang Anai, Kabupaten Padang Pariaman - Rangga Prayitno; Radiyan Rahim; Rica Azwar; April zahmi; Ade Triawan; Gustri Efendi (LPPM Universitas Ekasakti, 2025)
Violence against children and women is a serious issue that threatens welfare, security, and human rights. In Padang Pariaman Regency, particularly in Nagari Kasang, cases still occur that reflect the community's low awareness of legal protection mechanisms. This outreach activity aims to increase public understanding of legal protection for children and women in accordance with Law No. 23 of 2004 on the Elimination of Domestic Violence and Law No. 35 of 2014 on Child Protection. The implementation methods included interactive legal lectures, group discussions, educational video screenings, and case reporting simulations to the authorities. Evaluation results from pre-tests and post-tests indicated a significant improvement in participants’ legal knowledge, from an average of 58% to 87%. The community also demonstrated increased awareness in reporting violence cases to the relevant authorities. Supporting factors included the commitment of local government officials and participants’ enthusiasm, while challenges faced were patriarchal culture and limited complaint facilities. This activity proves that community-based participatory outreach is effective in promoting violence prevention and strengthening legal protection for victims.